ПРИНЦИПИ ВИДІЛЕННЯ І ПРОСТОРОВО-ЧАСОВІ МЕЖІ КАЙНОЗОЙСЬКИХ БУРОВУГІЛЬНИХ ФОРМАЦІЙ В МЕЖАХ ПІВДЕННО-ЗАХІДНОЇ ЧАСТИНИ СХІДНОЄВРОПЕЙСЬКОЇ ПЛАТФОРМИ - Aleksandrova, A. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2013)
The Paleogene-Neogene lignite formations were allocated substantiating the characteristics of their composition, structure, distribution, development, and relationships with adjacent no-coals formations Given the significant geological study materials Cenozoic industrial coal-bearing deposits within the coating megastructures southwestern part of the East-European platform.